Nicorandil in the prevention of cardiac damage and type 4A myocardial infarction with planned percutaneous coronary intervention in patients with atherosclerosis of coronary arteries - G. N. Soboleva; R. V. Gostishchev; A. N. Rogoza; T. I. Kotkina; A. N. Samko (Российский кардиологический журнал, 2019)
Aim. To study the possibility of reducing the risk of intraoperative cardiac damage and 4a type myocardial infarction (MI) by administering the oral nicorandil in patients with a stable form of coronary artery disease (CAD) before planned percutaneous coronary intervention (PCI).Material and methods. The study included 182 patients with stable CAD who were randomized to the nicorandil treatment group (n=90) and the control group with a standard treatment (n=92). Nicorandil was prescribed 2 days before PCI (30 mg/day); on the day of PCI — 2 hours before surgery (20 mg orally), 6-12 hours after PCI — 10 mg, later — 30 mg/day within 30 days. The analysis of highly sensitive troponin I (hs-troponin) and creatine kinase-MB (CK-MB) was carried out before PCI and 24, 72 hours after the procedure, the type 4a diagnosis of MI was established according to fourth universal definition.Results. The rate of hs-troponin after 24 hours exceeded the 99th percentile from the upper limit of normal in 146 patients (80%). In the control group, there was a statistically significant more frequent increase in hs-troponin by more than 2000 ng/ml (10% of patients in the control group versus 1% of the patient in the nicorandil group, p=0,038). Type 4a MI was detected in 12% of patients in the control group, and it decreased to 3% of patients in the nicorandil group (p=0,05), and in women it was observed in 21% in the control group and in 3% in the nicorandil group. Among women (n=61), the increment of hs-troponin 24 hours after PCI was statistically significantly lower (287 versus 1135 pg/ml, p=0,04) in the nicorandil group compared to the control group.Conclusion. Reducing the risk of cardiac damage and 4a type MI by nicorandil using before PCI, compared with standard antianginal therapy, is an effective tool in cardioprotection of patients with stable CAD before planned PCI.